Evaluasi Status Kerusakan Tanah Sawah Berbasis Sistem Informasi Geografis di Kecamatan Baturiti Kabupaten Tabanan, Provinsi Bali - RENI ANDRIANI NAIBAHO; NI MADE TRIGUNASIH; I WAYAN NARKA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Evaluation of the Damage Status of Rice Fields Based on Geographic Information Systems in Baturiti District, Tabanan Regency Soil damage is a change in the basic properties of the soil that exceeds the standard criteria for soil damage. This study aims to determine the potential damage to paddy fields, the status of damage to paddy fields, and to make a map of the potential and status of damage to paddy fields. The research was conducted using survey and scoring methods, homogeneous land unit maps were made to determine the sampling point. Based on the results of overlapping maps of slope, soil type, land use and rainfall data, 5 points of homogeneous land units were obtained. Field observations were made to determine the parameters of the thickness of the solum and surface rock, composite soil sampling for analysis of pH, texture, electrical conductivity, number of microbes and intact soil samples for analysis of permeability, bulk density, and porosity. The results of the research on potential soil damage were classified as mild at SLH 1 (Perean Tengah) and 5 (Apuan) and moderate at SLH 2 (Antapan), 3 (Luwus) and 4 (Batunya). The soil damage status was classified as light at SLH 3 (Luwus) with the limiting factor of porosity, SLH 1 (Perean Tengah) and 5 (Apuan) with the limiting factor of permeability. SLH 2 (Antapan) and 4 (Batunya) are not damaged.